2013
DOI: 10.1182/blood.v122.21.2966.2966
|View full text |Cite
|
Sign up to set email alerts
|

Improving Recognition, Diagnosis, and Management Of Heparin Induced Thrombocytopenia By Implementing a Computer-Based Clinical Decision Support System

Abstract: Introduction Heparin induced thrombocytopenia (HIT) is often not considered as a potential etiology of thrombocytopenia. The gradual 5 to 14 day decline in platelet count (PC) may not be easily recognized by busy clinicians. The life-threatening complications of HIT are potentially preventable with prompt recognition and management. Implementation of computer-based clinical decision support systems (CDSS) may aid in addressing these issues. Such systems have shown promise in increasing provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Neither of these studies compared their HIT CDS systems with a validated pretest risk score such as the 4Ts score. An additional study using CDS to identify patients with a 50% platelet count drop showed that only 38% of the patients identified by the alert had an intermediate or high 4Ts score . All three of these studies utilized CDS systems that evaluated only the magnitude of thrombocytopenia without considering the timing of platelet count fall.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these studies compared their HIT CDS systems with a validated pretest risk score such as the 4Ts score. An additional study using CDS to identify patients with a 50% platelet count drop showed that only 38% of the patients identified by the alert had an intermediate or high 4Ts score . All three of these studies utilized CDS systems that evaluated only the magnitude of thrombocytopenia without considering the timing of platelet count fall.…”
Section: Discussionmentioning
confidence: 99%